2014
DOI: 10.1590/s0100-06832014000600017
|View full text |Cite
|
Sign up to set email alerts
|

Doses, fontes e épocas de aplicação de nitrogênio influenciando teores de clorofila e produtividade do trigo

Abstract: RESUMO Para obter altas produtividades de trigo, são necessários o manejo correto da adubação nitrogenada e a utilização de cultivares de alto potencial produtivo. Sendo assim, objetivou-se avaliar doses e fontes de nitrogênio (N), aplicadas totalmente em semeadura ou em cobertura, na produção e nos seus componentes em dois cultivares de trigo irrigado, em sistema de plantio direto, cultivado numa região de cerrado de baixa altitude. O delineamento experimental foi em blocos ao acaso, em esquema fatorial 5 × 3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
14
0
10

Year Published

2017
2017
2020
2020

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 29 publications
(30 citation statements)
references
References 16 publications
4
14
0
10
Order By: Relevance
“…Similar results were reported by Teixeira Filho et al (2008) and Theago et al (2014), who observed that the N rates did not affect these parameters, and by Nunes et al (2015), who found that the N rates (in topdressing) did not affect the mass of 1,000 grains in areas with high N availability. Frank & Bauer (1996) observed that, in the period between the emergence of seedlings and the differentiation of panicles, N deficiency reduced the mass of 1,000 grains.…”
Section: Resultssupporting
confidence: 89%
See 3 more Smart Citations
“…Similar results were reported by Teixeira Filho et al (2008) and Theago et al (2014), who observed that the N rates did not affect these parameters, and by Nunes et al (2015), who found that the N rates (in topdressing) did not affect the mass of 1,000 grains in areas with high N availability. Frank & Bauer (1996) observed that, in the period between the emergence of seedlings and the differentiation of panicles, N deficiency reduced the mass of 1,000 grains.…”
Section: Resultssupporting
confidence: 89%
“…The N rates also affected the number of grains per spike. Similar results were obtained by Theago et al (2014), who reported that the increase in N levels (in topdressing) at a rate of up to 128 kg ha -1 produced the largest number of grains per spike and spikes per meter, irrespective of the N source used.…”
Section: Resultssupporting
confidence: 87%
See 2 more Smart Citations
“…Conventional urea and Super N showed similar results in wheat grain yield (Table 1), which agree with Megda et al (2009) and Theago et al (2014). Prando et al (2012), evaluating sources of urea, urea + NBPT, and coated urea in temperate climatic conditions, did not observe changes in yield, grain mass, number of spikes per m 2 , and plant height, but partially obtained results similar to the present study.…”
Section: Productivity Of Wheat Grainssupporting
confidence: 89%